Conceptual framework for Shari'ah corporate governance with special focus on Islamic capital market in Malaysia - Kasim, Nawal; Htay, Sheila Nu Nu; Syed, Ahmed Salman (International Association of Computer Science and Information Technology (I A C S I T), 2013)
Corporate governance issue emerged with the birth of the corporations. Similarly, the need for Shari’ah corporate governance is given attention by the regulators, industrial players, Shari’ah advisors and researchers with the bloom of Islamic finance. There are limited literature and Shari’ah governance guidelines available for Islamic financial institutions. The existing guidelines are general and they not as specific as conventional guidelines. In addition, there is no Shari’ah governance guideline for Islamic capital market in Malaysia. Therefore, this paper aims to propose conceptual framework for Shari’ah corporate governance with special focus on Islamic capital market by integrating the conventional concepts of governance. We believe that the concept of Islamic accountability, independency, competency and transparency should be the basic foundation in developing the conceptual framework for Shari’ah corporate governance.